Perilaku Harian Simpai (Presbytis melalophos) dalam Kandang Penangkaran - -, Wirdateti; Dahruddin, Hadi (Jurnal Veteriner; Vol 12, No 2 (2011))
Mitred Leaf Monkey (Presbytis melalophos) is one of species from genus Presbytis, existing on theisland of Sumatra, which lives in primary forests in the interior ranging from lowland altitude till 2500 mabove of the sea level. The main food of the animal is fruits, and young leaves. Besides, they also eatflowers, seeds, shoots, and some species of insects. This species has social groups that can consist of oneor several males and several females. Mitred Leaf Monkeys spend more than half day resting and feedingfruits and young leaves. The purpose of this study was to determine the behavior and activities of theMitred leaf Monkey in captivity in order to stimulate the animal breeding out of their natural habitat. Theresearch was using One-Zero Sampling methods that noted every activity (behaviours) during a specificperiod of the time. The behaviour observation was eating, grooming, locomotion, defecation, urination anddrinking. The results showed that, the main activities were locomotion with average 27.93%, 25.57% forgrooming, and 24.425% for feeding. The positional behavior of the animals was characterized byquadrupedalism as the major locomotion mode, while sitting was the most common posture when theywere resting and feeding.
Keywords: Presbytis melalophos, behavior, locomotion, feeding, grooming.